Body Matters. - Asdam, Knut; Balkenhol, Bernhard; Claerbout, David; Higgs, Matthew; Iles, Chrissie; Kroksnes, Andrea; Norment, Camille; Payne, Oliver; Relph, Nick; Wilson, Andrew (Oslo : National Museum of Contemporary Art Oslo, 2003)
Abramovic, Marina ; Beecroft, Vanessa ; Claerbout, David ; Hill, Gary ; Kuitenbrouwer, Mirjam ; Land, Peter ; Lind, Victor ; Norment, Camille ; Payne, Oliver ; Relph, Nick ; Wallinger, Mark ; Ytterstad, Snorre ; Asdam, Knut
Engels
Noors
Exhibition. Body Matters. National Museum of Contemporary Art Oslo, 11.01.2005 - 11.05.2003.
boek